Mayo registry for telemetry efficacy in arrest study: An evaluation of the feasibility of the do not intubate code status. (1st October 2016) - Snipelisky, David; Dumitrascu, Adrian; Ray, Jordan; Roy, Archana; Matcha, Gautam; Harris, Dana; Vadeboncoeur, Tyler; Kusumoto, Fred; Burton, M. Caroline
ABSTRACT: Introduction: Guidelines recommend discussing code status with patients on hospital admission. No study has evaluated the feasibility of a full code with do not intubate (DNI) status. Methods: A retrospective analysis of patients who experienced a cardiopulmonary arrest was performed between May 1, 2008 and June 20, 2014. A descriptive analysis was created based on whether patients required mechanical ventilatory support during the hospitalization and comparisons were made between both patient subsets. Results: A total of 239 patients were included. Almost all (n = 218, 91.2%) required intubation during the hospitalization. Over half (n = 117, 53.7%) were intubated on the same day as the cardiopulmonary arrest and 91 patients (41.7%) were intubated at the time of arrest. Comparisons between intubated and non-intubated patients showed little differences in clinical characteristics, except for a higher proportion of medical cardiac etiology for admission in patients who did not require intubation (n = 10, 47.6% versus n = 55, 25.2%; p = 0.18) and initial arrest rhythm of ventricular tachycardia/fibrillation (n = 8, 38.1% versus n = 50, 22.9%; p = 0.37). No differences in 24-hour and posthospital survivals were present. Conclusion: Mechanical ventilatory support is commonly utilized in patients who experience a cardiopulmonary arrest. The DNI status may not be a feasible code status option for most patients.